What moves social movements? The role of emotions in collective action - Demertzis, Nicolas (Επιστήμη και Κοινωνία: Επιθεώρηση Πολιτικής και Ηθικής Θεωρίας, 2021)
For many years, the study of emotions as a means of understanding social movements has been treated with suspicion, as emotions in politics were stereotypically associated with irrationalism and the worst moments and aspects of European and world history (i.e., Fascism, Nazism, populism). Even during the 1980s and most of the 1990s, when the study of social movements was at its peak, affective factors were rarely mentioned. This distrust has largely been dispelled over the last twenty years or so, as the sociology of emotions has rapidly developed. Movement analysis could not remain unaffected by this shift, and from the late 1990s on, a growing number of related works have reset the agenda in movement research. Specific emotions elicited within certain movements have been centre-staged: hope, frustration, disgust, contempt, hatred, devotion, fear, shame, rage, resentment, excitement, trust are but a few of the prevalent emotions that are now being used to explain the movement dynamics. In a way, this marks the return of the repressed to the analysis of social movements. Premised on the appraisal theory of emotions, this paper will discuss protest emotions as accelerators and amplifiers of social movements.